The Role of TGF-β in Polycystic Ovary Syndrome. (January 2014) - Raja-Khan, Nazia; Urbanek, Margrit; Rodgers, Raymond J.; Legro, Richard S.
Polycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by chronic oligoanovulation and hyperandrogenism and associated with insulin resistance, type 2 diabetes, and cardiovascular risk. In recent years, genetic studies have linked PCOS to a dinucleotide marker D19S884 in the fibrillin 3 gene. Fibrillins make up the major component of microfibrils in the extracellular matrix (ECM) and interact with molecules in the ECM to regulate transforming growth factor β (TGF-β) signaling. Therefore, variations in fibrillin 3 and subsequent dysregulation of TGF-β may contribute to the pathogenesis of PCOS. Here, we review the evidence from genetic studies supporting the role of TGF-β in PCOS and describe how TGF-β dysregulation may contribute to (1) the fetal origins of PCOS, (2) reproductive abnormalities in PCOS, and (3) cardiovascular and metabolic abnormalities in PCOS.